Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/eci.12030
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index is highly associated with adiponectin values and glycaemic disturbances

Abstract: We report for the first time the direct relations of VAI with adipose tissue secretion, as well as with functional glycaemic disorders. Because VAI is estimated easily with data obtained in everyday practice, it could be used as an indirect index of adiponectin levels and the risk of impaired glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
43
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 26 publications
9
43
1
5
Order By: Relevance
“…In our study, the examined obesity measures showed consistent associations with age, blood pressure, adipokines, HOMA-IR, and CRP; however, there was a trend for superiority (stronger correlation coefficients and independent predictive value in multivariate analyses) for BMI (mainly) and WC relative to VAI and waist-hip ratio. VAI is independently associated with glucose values, a finding that has been reported from our group in a recent study in adults (22); however, this finding cannot establish its predictive value concerning the future emergence of impaired glucose tolerance and/or diabetes. On the other hand, BMI-an index of overall adiposity-was strongly associated with leptin values, which in turn demonstrated the strongest correlations with insulin resistance and subclinical inflammation.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In our study, the examined obesity measures showed consistent associations with age, blood pressure, adipokines, HOMA-IR, and CRP; however, there was a trend for superiority (stronger correlation coefficients and independent predictive value in multivariate analyses) for BMI (mainly) and WC relative to VAI and waist-hip ratio. VAI is independently associated with glucose values, a finding that has been reported from our group in a recent study in adults (22); however, this finding cannot establish its predictive value concerning the future emergence of impaired glucose tolerance and/or diabetes. On the other hand, BMI-an index of overall adiposity-was strongly associated with leptin values, which in turn demonstrated the strongest correlations with insulin resistance and subclinical inflammation.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, this index seems to have predictive value in terms of an increased risk for cardiovascular events (13) and has served as a marker of insulin resistance in several different nosologic entities (16)(17)(18)(19)(20)(21). Furthermore, our group recently reported, for the first time, the strong relationship of VAI with adipose tissue secretion and with functional glycemic disorders (22).…”
mentioning
confidence: 83%
“…However, despite this evidence, the VAI in CS has a strong application limit. The reason for this is that it is an indicator of early cardiometabolic risk and an important diagnostic tool in all borderline conditions in which overt MS is not present (32). Indeed, in our cohort of CS patients, 62.9% had overt MS, and so the VAI cannot be considered a specific index for these patients.…”
Section: Discussionmentioning
confidence: 88%
“…Поэтому, в настоящее время предложены неинвазивные методы оценки выраженности висцераль-ного ожирения. Индикатором дисфункции жировой ткани при этом может являться расчетный индекс висцераль-ного ожирения [5,7,8], включающий антропометричес-кие (индекс массы тела и объем талии) и функциональ-ные (уровень триглицеридов и холестерина липопротеи-нов высокой плотности) показатели, свидетельствующие о распределении функции жировой ткани* [6].…”
unclassified